Behavior of Cu20O particles in Copper Smelting Heat Recovery Boiler Conditions - E. J. Peuraniemi (The Minerals, Metals and Materials Society, 2001)
Primary copper production using suspension smelting techniques like Outokumpu Flash Smelting always causes some dust formation. Flue dust particles are formed when sulphide feed material reacts violently with oxygen inducing particle disintegration and total desulphurisation of fragments. In the process, flue dust follows the off-gases to the heat recovery boiler (HRB) where its sulphation takes place because of prevailing conditions. Sulphation releases heat and causes also a drop in particle melting temperature and, further, particle sticking to the walls and heat exchange tube banks. Sulphation of synthetic CU20 particles were examined using a laboratory scale fluid-bed reactor. This study aims to a better understanding of flue dust behaviour in a HRB and, thus, to a better operational practise and design of a HRB. The effect of PSO/PO2 -ratio and temperature on the sulphation kinetics were tested. Standard chemical analysis, light optical and scanning electron microscopy with energy dispersive spectroscopy were used to examine the samples.